Harmonia axyridis (Coleoptera: Coccinellidae) in Serbia: its presence on aphid-infested plants and co-occurrence with native aphidophagous coccinellids: Harmonia axyridis in Serbia - Jovičić, Ivana; Radonjić, Anđa; Kljajić, Petar; Andrić, Goran; Pražić Golić, Marijana; Petrović-Obradović, Olivera (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2021)
The presence of the invasive coccinellid Harmonia axyridis in aphid colonies on plants, as well as its co-occurrence with native coccinellid predators was studied in the period 2011-2020. Also, its occurrence on fruit plants and grapes was monitored at harvest time. Research was conducted on 41 locations in Serbia. The feeding of this invasive species was recorded on a total of 43 aphid taxa of 25 different genera. It was most frequently present on aphid colonies of the genera Aphis, Brachycaudus and Myzus. The presence of H. axyridis in aphid colonies was recorded on 58 cultivated plant species: 10 fruit, 7 field crop, 5 vegetableand 16 ornamental species, as well as 20 non-cultivated plants. Harmonia axyridis feeding was also observed on mature fruit plants of cultivated blueberries, nectarine and grapes in representative production areas in Serbia. Nine native coccinellid species were detected in this study: Adalia bipunctata, Adalia decempunctata, Coccinella septempunctata, Hippodamia sp., Hippodamia apicalis, Hippodamia variegata, Hippodamia tredecimpunctata, Hippodamia undecimnotata and Propylea quatuordecimpunctata. Populations of H. axyridis and native coccinellids co-occurred in aphid colonies on many plants, i.e. in 53.45% of all samples. The results inferred that H. axyridis as a predator of numerous aphids on many plants is a useful coccinellid species. However, it may also be considered as a potential pest in fruit and grape production, and a threat to native aphidophagous coccinellids.
Keywords: harlequin ladybird, Coccinellidae, Aphididae, host plants, predatory insects